Purification and Long-Term Expansion of Multipotent Endothelial-Like Cells with Potential Cardiovascular Regeneration. - Marchal, Juan Antonio; Picón, Manuel; Perán-Quesada, Macarena; Bueno, Clara; Jiménez-Navarro, Manuel Francisco; Carrillo, Esmeralda; Boulaiz, Houria; Rodríguez-Losada, Noela; Álvarez, Pablo; Menéndez, Pablo; De-Teresa-Galván, Eduardo; Aránega, Antonia (My University, 2011)
Endothelial progenitor cells (EPC) represent a relatively rare cell population, and expansion of sufficient cell numbers remains a challenge. Nevertheless, human adipose-derived stem cells (hASC) can be easily isolated and possess the ability to differentiate into endothelial cells. Here, we propose the isolation and characterization of multipotent endothelial-like cells (ME-LC) with the capacity to maintain their vascular progenitor properties for long periods. hASC were isolated from lipoaspirates and cultured through distinct consecutive culture stages for 2 months to enrich ME-LC: first in Dulbecco's modified Eagle's medium–fetal bovine serum (stage I), followed by a stage of culture in absent of fetal bovine serum (stage II), a culture in SFO3 medium (stage III), and, finally, the culture of ME-LC into collagen IV-coated flasks in endothelial growth medium (EGM-2) (stage IV). ME-LC display increased expression levels of endothelial and hematopoietic lineage markers (CD45, KDR, and CXCR4) and EPC markers (CD34 and CD133), whereas the expression of CD31 was barely detectable. Reverse transcription (RT)-polymerase chain reaction assays showed expression of genes involved in early stages of EPC differentiation and decreased expression of genes associated to differentiated EPC (TIE-2, DLL4, and FLT-1). ME-LC formed capillary-like structures when grown on Matrigel, secreted increased levels of stromal cell-derived factor-1 (SDF-1), and showed the ability to migrate attracted by SDF-1, vascular endothelial growth factor, and hematopoietic growth factor cytokines. Importantly, ME-LC retained the capacity to differentiate into cardiomyocyte-like cells. We present a simplified and efficient method to generate large numbers of autologous ME-LC from lipoaspirates-derived hASC, opening up potential cell-based therapies for cardiovascular regenerative medicine.
https://openpolicyfinder.jisc.ac.uk/id/publication/164
Keywords: Células madre; Sistema cardiovascular - Regeneración; Regeneration; Multipotent stem cells